PENGARUH CAPITAL ADEQUACY RATIO (CAR), LOAN TO DEPOSIT RATIO (LDR), NON PERFORMING LOAN (NPL), RETURN ON ASSET (ROA), NET INTEREST MARGIN (NIM), DAN BIAYA OPERASIONAL PENDAPATAN OPERASIONAL (BOPO) TERHADAP PEMBERIAN KREDIT (Studi Kasus Pada PD. BPR BKK P - Lusia Estine Martin; Saryadi Saryadi; Andi Wijayanto (Jurnal Ilmu Administrasi Bisnis, 2014)
Business competition more stringent demand of a bank to improve its performance in order to attract investor. Investors before sinking their capital requires information about the performance of companies. The ratio of financial analysis such as CAR, LDR, NPL, ROA, NIM and BOPO an alternative to test whether reduce its financial can be used to perform a prediction against the provision of credits the future. The ratio CAR, LDR, NPL, ROA, NIM and BOPO devired from internal condition bank concerned. When the factors in a state of healthy and the bank can be achieved. The problem in this research is the existence of dissent from the results of previous researches. The purpose of this research is to analyze influence CAR, LDR, NPL, ROA and BOPO to Credit Loan on PD. BPR BKK Pati City period 2007 – 2012.The data used is data secondary quarter from the financial report published by the PD. BPR BKK Pati City. The technique of the sample is purposive of sampling. Techniques that we use is linear regression analysis.Based on the linear regression worship of idols this research concludes that capital adequacy ratio, loan to deposit ratio and the operational cost operational income influential positive and significantly to the provision of credit. Meanwhile, non performing loan and return on assets negative effects and significantly to the provision of credit while net interest margin negative effects and insignificant against the provision of credit. Simultaneously there is significant influence between CAR, LDR, NPL, ROA, NIM and BOPO to Credit Loan with a coefficient determination of 0,960.Suggestion that can be conveyed based on the result analysis indicated that the management of the bank NPL ratio and ROA, it is necessary to pay close attention to because both the ratio of the bank financial is variable the most dominant and consistent in effecting a decrease in credit loan. While factors that affects the increase in credit loan is CAR, LDR, BOPO. This can be used as guidelines either by the company management, in the management of the company and by investors in determining an investment strategy.